Bioaccumulation of polybrominated diphenyl ethers by Tubifex Tubifex - Kolar, Boris (Acta chimica slovenica, 2016)
The selective uptake of polybrominated diphenyl ethers (PBDEs) by oligochaetes makes it possible to assess the bioaccumulation of individual congeners in commercial mixtures. Twenty-one congeners from three BDE commercial mixtures (TBDE-71, TBDE-79 and TBDE-83R) and as individual congeners (BDE-77, BDE-126, BDE-198 and BDE-204) were tested on Tubifex tubifex in accordance with the OECD TG 315 "Bioaccumulation in Sediment-Dwelling Benthic Oligochaetes". All the congeners that were spiked in the sediment were detected at the end of the uptake phase and at the end of the experiment. The bioaccumulation factor (BAF), the kinetic bioaccumulation factor (BAFK) and the biotasediment accumulation factor (BSAF) were calculated, and indicate a high bioaccumulation potential for tri- to hexa- BDEs and a lower bioaccumulation potential for hepta- to deca-BDEs. The penta-homologues BDE-99 and BDE-100 showed the highest BSAFs of 4.84 and 5.85 (BAFs of 7.34 and 9.01), while the nona- and deca-BDEs exhibit bioaccumulation in up to one-order-lower concentrations. The change in the bioaccumulation potential between the group of trito hexa-BDEs and hepta- to deca-BDEs correlated with the generally accepted molecular-mass threshold for the molecular transition through biological membranes (700 g/mol).
Keywords: Bioaccumulation; BSAF; polybrominated diphenyl ethers; Tubifex tubifex